Teologi Perdamaian dalam TafsÃ®r Jihad - Wasid, Wasid (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The presence of Islam within humanity space would, in fact, lead to the creation of life order to fulfill tawhîd and peace of the world. The problem of tawhîd is the very core of life, though its meaning has, sometimes, tended to be theocentric by neglecting anthropocentric dimension. It can be observed through ideological reasoning of radicalism group in defining jihâd as a means of struggle to uphold oneness of God, though this group put less interested in presenting Islam within principles of peace. It suggests that oneness of God (tawhîd) is purely intended to Him and it has no relation with human. This problem needs to be re-observed, if not to be sued, by looking at universal values from the presence of Islam in which it has been so far known as highly honoring peace and values of humanity as well as values of divinity.